Daniel, Lost Revolutions - The South In The 1950s - Gilmartin, Daniel (Teaching History: A Journal of Methods, 2004)
Lost Revolutions characterizes the two decades following World War II as a period of missed opportunity in terms of racial relations in the postwar South. Daniel grapples with mercurial and sometimes contradictory evidence in trying to make a case that racial relations in the South could have been very different. While providing much discussion and anecdote that is worthwhile to the teacher of U.S. history, he fails to convince the reader of the validity of his main assertion.